The effect of time administration and concentration of probiotics of the growth and yield of suri cucumber plants (Cucumis melo L. var reticulatus Naudin). - Iswita Iswita; Susylowati Susylowati; Eliyani Eliyani (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
Suri cucumber (Cucumis melo L. var reticulatus Naudin) is an annual plant. Probiotics is not a fertilizer in general, but materials containing effective microorganism that can help decompose the material present in the soil and can be used to inhibit the growth of plant pests and diseases in the soil, this study aims to determine: (1) the interaction between time and concentration on growth and yield on suri cucumber plants; (2) Time of giving probiotics that are appropriate for growth and yield on suri cucumber plants; and (3) Probiotic concentrations that are appropriate for growth and yield on suri cucumber plants. This research was conducted from April to July 2018 at the Kelurahan Loa Tebu, Kecamatan Tenggarong, Kabupaten Kutai Kartanegara. Factorial designs are arranged in Complete Randomized Design (CRD) with 6 replications. The first factor is the time administration of (W) probiotics at 7 am 12(w1) "> and 4 pm 12(w2)"> . The second factor is the concentration of (K) probiotics: : 0 ( 12k0"> ), 5 ( 12k1"> ),10 ( 12k2"> ) and( 12k3)"> 15 mL. 12L-1">  water. Variables observed in this study were plant height increase, number of leaves, fruit diameter, number and weight of fruit crops. The data were analyzed by analysis of variance (Anova), If the result of Anova showed significantly different, continued by Least Significant Difference(LSD) test at the 5% level to compare between two average treatments.. The results showed that (1) no interaction between the time administration and theconcentrationof probiotics on the growth and yield of cucumber plants on all of the observed variables, namely plant height increase, number of leaves, fruit diameter, number of fruit crops, weight of planting fruit; (2) the time of probiotic administration that has a significant effect on the variable plant height increase at 4 pm; and (3) the treatment of probiotic concentration has no significant effect on all observed variables.